Sightwitch : the true tale of the twelve paladins - Dennard, Susan (Dennard, Susan. Witchlands novel., 2018)
Set a year before Truthwitch, Sightwitch follows Ryber Fortiza, the last Sightwitch Sister as she treks deep underground to rescue her missing best friend. While there, she encounters a young Nubrevnan named Kullen Ikray, who has no memory of who he is or how he wound up inside the mountain. From the New York Times bestselling author of Windwitch Susan Dennard, an illustrated prequel novella set in the Witchlands setting up the forthcoming hotly anticipated Bloodwitch.